Digital degradation: Stigma management in the internet age. (January 2018) - Lageson, Sarah E; Maruna, Shadd
The concept of stigma and labeling has been central to the sociology of punishment since at least the writings of Durkheim and Mead. However, the vast transformations brought on by the expansion of the internet over the past 20 years suggest the need for revisiting the dynamics of labeling. While the power to apply extralegal criminal labels is now in the hands of many, stigma in the form of a digital footprint is arguably more difficult than ever to escape. This paper draws on two small studies to better understand these new dynamics of labeling: a discourse analysis of the motivations of online labelers and interviews with individuals struggling to cope with online labels. This evidence describes how the internet has become a fertile space for the expression of public anxieties about social problems and a digital prison that can discourage the labeled from engaging with the processes of reintegration.